2018
DOI: 10.21608/ejvs.2018.5311.1049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Joint Inflammation on Piroxicam Pharmacokinetics in Rats

Abstract: In conclusion: Piroxicam in dose of 20mg/kg/ b.wt via i.m has an antiinflammatory effect in rat with joint inflammation and has non-significant higher and prolonged plasma concentration in inflamed joint rats than in normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(34 reference statements)
1
1
0
Order By: Relevance
“…Amer et al, highlight the importance of the Piroxicam in reducing the joint in ammation associated with arthritis [9]. The in amatory mediators, arthritic score and paw edema were reduced as a result in this study.…”
Section: Camp Signi Cantly Reduced Pge2supporting
confidence: 60%
“…Amer et al, highlight the importance of the Piroxicam in reducing the joint in ammation associated with arthritis [9]. The in amatory mediators, arthritic score and paw edema were reduced as a result in this study.…”
Section: Camp Signi Cantly Reduced Pge2supporting
confidence: 60%
“…It has proven in their study that there was a statistically significant difference (p<0.05) of joint swelling and PGE2 level in IA piroxicam treated rats as compared to IA saline treated rat models of OA 17 . Likewise research work of Aziza and Hana revealed that IM therapy of piroxicam reduces joint edema and arthritic index statistically significantly (p<0.05) in Freud Adjuvant induced arthritis models of rat 18 . Their findings also strengthen our results regarding chondroprotective efficacy of piroxicam.…”
Section: Discussionmentioning
confidence: 83%